A Comparative Research on the Energy Recovery Potential of Different Vehicle Energy Regeneration Technologies. (February 2019) - Yu, Wei; Wang, Ruochen; Zhou, Runze
Abstract: Researches on various energy regeneration technologies applied on vehicles have been conducted by many scholars. However, the comprehensive study of these technologies on a single vehicle at the same time was rarely paid attention to. This paper proposes a comprehensive vehicle energy regeneration system consists of regenerative braking, suspension vibration energy recovery and exhaust waste heat recovery. The energy recovery model is developed to explore the energy recovery potential and the ability of these three subsystems on a mild hybrid vehicle. Based on the comparative simulation results, regenerative braking and energy regenerative suspension are highly affected by the actual driving conditions. By contrast, the performance of exhaust waste heat recovery system is more stable because the exhaust temperature and mass flow rate change gently with the various driving conditions. Meanwhile, the integration of different energy recovery technologies can maximize the energy saving effect.